Vertical product differentiation and social health systems in a market for prescription drugs: Revised version of a talk given at the 2. World Congress on Health Economics in Zürich, Sept. 10 - 14, 1990 - Anette Boom (Universität Konstanz, Fakultät für Wirtschaftswissenschaften und Statistik, 1990)
Following models of vertically differentiated duopoly this paper deals with the influence of a social health system on the sustainability of the duopoly and on the respective prices. Emphasis is laid on the effect of a reduction of the coinsurance rate for drugs on prices and on the market structure. The results depend on the size of the relative effect such a reduction has on the rate of the disposable income. The social health system is assumed to be financed by deductions from the income of the insured. Conclusions are drawn with respect to different health systems.
Keywords: 330